Commander-in-chief eaudiobook - Greaney, Mark (Jack Ryan,, 2015)
This electrifying thriller in the #1 New York Times  bestselling series has President Jack Ryan and his allies facing a treacherous foe threatening to unleash chaos around the globe... When Russian President Valeri Volodin’s ambitions are foiled in Dagestan, he faces a difficult choice. The oligarchs who support him expect a constant flow of graft, but with energy prices cratering, the Russian economy sputters to a virtual halt. Unable to grow the Russian market at home, his hold on power relies on expansion abroad—a plan that has been thwarted by the United States in the past. But this time Volodin has determined that an indirect approach is the best. A floating natural gas facility in Lithuania is blown up. A Venezuelan prosecutor is assassinated. A devastating attack on a Russian troop train kills dozens. A chaotic world is the best camouflage for a series of seemingly unrelated attacks. Only one man recognizes an ominous pattern in the reports of terror from around the globe. U.S. President Jack Ryan sees a guiding hand in the worldwide chaos, but before he can act he needs proof. While his intelligence agencies race to uncover the truth behind the attacks, the President struggles to unite a fractious and distrustful coalition of Western nations against the schemes of the Russian dictator. With five thousand Russian troops poised to invade a NATO nation, can Jack Ryan move swiftly enough to stop Volodin’s grand plan of global conflict and conquest? Or will he succeed in changing the balance of world power forever?